The effect of microwave on dimensional accuracies of maxillary denture bases (2014)
Objective: This study was carried out to investigate the effect of different microwave powers on dimensional accuracies of sampled maxillary acrylic resin bases. Method: Maxillary acrylic resin bases were constructed on stone casts previously made from a prefabricated rubber mould. Dimensions of the cast-acrylic resin assemblies were taken at designated points with digital caliper. The acrylic bases were then subjected to simulated disinfection under different microwave powers and time periods, after which they were returned to their casts and post microwave measurements taken at the same designated points. Result: The highest mean (±SD) of dimensional discrepancies (0.082±0.03) was observed in the mid-palatal region of the maxillary bases at 690W/6minutes regimen while the lowest was at the right crest (0.012±0.02).The dimensional distortion at the mid-palatal region was statistically significant compared to other measurement points. Conclusion: The mid-palatal region of the maxillary bases which shows the greatest tendency to undergo significant distortion is unfortunately the area that makes one of the greatest contribution to the retention of upper dentures by way of close adaptation to the palatal tissue.